Functional Wetland Loss Drives Emerging Risks to Waterbird Migration Networks - Donnelly, J. Patrick; Moore, Johnnie N.; Casazza, Michael L.; Coons, Shea P. (Frontiers in Ecology and Evolution, 2022)
Migratory waterbirds (i.e. shorebirds, wading birds, and waterfowl) are particularly vulnerable to climate and land-use change. Life history strategies supported by an interdependent network of diffuse geographic regions can expose waterbird populations to multiple independent risks throughout their range. Emerging bottlenecks raise concerns over sustainability of continental wetland networks as water scarcity triggers ecological effects misaligned with waterbird habitat needs. Here we use important wetland regions in Oregon and California, USA as a model system to examine impacts of these changes on waterbird migration networks in western North America. We monitored wetland hydrology and flooded agricultural habitats monthly from 1988 to 2020 using satellite imagery to quantify the timing and duration of inundation - a key delimiter of habitat niche values associated with waterbird use. Trends were binned by management practice and wetland hydroperiods (semi-permanent, seasonal, and temporary) to identify differences in their climate and land-use change sensitivity. Wetland results were assessed using 33 waterbird species to detect nonlinear effects of network change across a diversity of life cycle and habitat needs. Pervasive loss of semi-permanent wetlands acted as an indicator of systemic functional decline driven by cascading top-down effects of shifting ecosystem water balance. Shortened hydroperiods caused by excessive drying transitioned semi-permanent wetlands to seasonal and temporary hydologies—a process that in part counterbalanced concurrent seasonal and temporary wetland losses. In SONEC, expansion of seasonal and temporary wetlands associated with closed basin lakes offset wetland declines on other public and private lands, including wildlife refuges. Diving ducks, black terns, and grebes exhibited the greatest risk of habitat decline due to semi-permanent wetland loss that overlapped important migration, breeding, molting, and wintering periods. Shorebirds and dabbling ducks were beneficiaries of stable agricultural practices and top-down processes of functional wetland declines that operated collectively to maintain habitat needs. Outcomes from this work provide a novel perspective of wetland ecosystem change affecting waterbirds and their migration networks. Understanding the complexity of these relationships will become increasingly important as water scarcity continues to restructure the timing and availability of wetland resources in western North America.